A study on biological occupational hazards in emergency medicine in Hospital Universiti Sains Malaysia - Abuzied, Sami Osman (2015)
Background: Hazards in working environment have posed significant risk to health care workers (HCWs). Biological hazard is one of the hazards and exists in most departments in hospital, including Emergency Department (ED). The objectives of this study were to look at the prevalence of biological hazards in ED, determine the association of different work shift and different triage zones with type of biological hazards. The associated factors of blood-borne and non-blood-borne diseases were also being determined. Methodology This was a prospective study conducted from 1st August 2013 to 30th November 2013. All patients who presented to ED, Hospital Universiti Sains Malaysia (HUSM) were reviewed based on the ED records. Hospital records of the patients with biological hazards were traced and reviewed. Demographic data and type of biological hazards were collected and association of work shift and triage zone were also analysed. Final diagnosis of those with biological hazards was also being determined by reviewing discharge note of the patients. All the data were entered using SPSS based on the sample size of each type of biological hazards. In order to avoid missing data, work sheet form year 2013 from Microbiology department was reviewed for all patients with blood-borne biological hazards. Based on the registered number of the patients, their visits to ED HUSM were traced and correlated with the study period. All the data was collected using a standardised proforma form. Results: A total of 200 cases that presented to ED HUSM had biological hazards. Majority of the cases was Malay (96.5%) and community acquired pneumonia .Apart from CAP and scabies there were no statistically significant association between biological hazards and the different time of the work shift. Majority of CAP and scabies cases came during PM shift with the percentage of 42.6% and 78.1% respectively. Most of the biological hazards had statistically significant association with triage zone except Human immunodeficiency virus (HIV) and Hepatitis B virus (HBV). Majority of tuberculosis (TB), CAP and Hepatitis C virus (HCV) cases presented to yellow zone with the percentage of 54.6%, 42.6% and 48.7% respectively. Majority of scabies and impetigo cases presented to the green zone. Age and gender were significant association factors of blood-borne diseases. Conclusion: Yellow zone had higher biological hazards exposure for CAP, TB and HCV while green zone had higher exposure for scabies and impetigo to HCWs in ED HUSM. PM shift had higher exposure for CAP and scabies. Age and male gender were the only significant predictors for the blood-borne biological hazards exposure to the HCWs in ED HUSM.